The acute and chronic effects of resistance training with blood flow restriction on hormonal responses in untrained young men: A comparison of frequency - Sharifi, Saman; Monazzami, Amirabbas; Nikousefat, Zahra; Heyrani, Ali; Yari, Kheirollah (Cellular and Molecular Biology, 2020)
The present study aimed to determine the effect of low-intensity training with blood flow restriction (BFR) on the response rate of anabolic hormones. Forty healthy and untrained young men, aged 18 to 25 years old, were randomly divided into five groups: one session of BFR training (BFR1), two sessions of BFR training (BFR2), one session of resistance training without BFR (WBFR1), two sessions of resistance training without BFR (WBFR2), and the control group (without training). BFR groups had three sets of 20 repetitions with 20-30% 1RM, and none-BFR groups had three sets of 10 repetitions with 70-80% 1RM for six weeks. Both BFR1 and WBFR1 groups trained 3day a week (1 session in a day and three sessions a week), BFR2 and WBFR2 groups trained three days a week (but two sessions a day and six sessions in a week) and Control group did not perform any training. The mean changes in growth hormone(GH), testosterone(TS), and vascular endothelial growth factor (VEGF) hormones were determined by ELISA technique before, after a first training session and after six weeks of the training program. To the analysis of data, two way repeated measures ANOVA at a significant level of P<0.05 also were used. The results showed a significant increase in GH levels in each of the four training groups as compared with the pre-test and the control group after a first training session and after six weeks of the training program (P<0.05). There was no significant increase in TS levels in each of the four training groups, as compared with the pre-test and the control group in both acute and chronic TS response (P>0.05). Only the WBFR1 group did not significantly increase in VEGF levels after the first training session (P>0.05). In chronic VEGF response, there were no significant changes observed in all training groups as compared with the control group(P>0.05). Despite the effectiveness of low-intensity BFR training, such as high-intensity resistance training on hormonal responses, two sessions per day training with the same volume does not necessarily result in larger responses in all hormones than one session per day training.